Olfactory ensheathing cells seeded muscle-stuffed vein as nerve conduit for peripheral nerve repair: a nerve conduction study - Lokanathan, Yogeswaran; Ng, Min Hwei; Hasan, Shariful; Ali, Anuar; Mahmod, Mazzre; Htwe, Ohnmar; Syed Waseem Ahmad, Sharifah Roohi; Idrus, Ruszymah; Abdullah, Shalimar; Naicker, Amaramalar Selvi (Elsevier, 2014)
We evaluated bridging of 15 mm nerve gap in rat sciatic nerve injury model with muscle-stuffed vein seeded with olfactory ensheathing cells as a substitute for nerve autograft. Neurophysiological recovery, as assessed by electrophysiological analysis was faster in the constructed biological nerve conduit compared to that of autograft.